Enhancement of chondrogenic differentiation supplemented by a novel small compound for chondrocyte-based tissue engineering - Hamamoto, Shuichi (J Exp Orthop, 2020)
PURPOSE: Chondrocyte -based tissue engineering has been a promising option for the treatment of cartilage lesions. In previous literature, TD198946 has been shown to promote chondrogenic differentiation which could prove useful in cartilage regeneration therapies. Our study aimed to investigate the effects of TD198946 in generating engineered cartilage using dedifferentiated chondrocyte-seeded collagen scaffolds treated with TD198946. METHODS: Articular chondrocytes were isolated from mini pig knees and expanded in 2-dimensional cell culture and subsequently used in the experiments. 3-D pellets were then cultured for two weeks. Cells were also cultured in a type I collagen scaffolds for four weeks. Specimens were cultured with TD198946, BMP-2, or both in combination. Outcomes were determined by gene expression levels of RUNX1, SOX9, ACAN, COL1A1, COL2A1 and COL10A1, the glycosaminoglycan content, and characteristics of histology and immunohistochemistry. Furthermore, the maturity of the engineered cartilage cultured for two weeks was evaluated through subcutaneous implantation in nude mice for four weeks. RESULTS: Addition of TD198946 demonstrated the upregulation of gene expression level except for ACAN, type II collagen and glycosaminoglycan synthesis in both pellet and 3D scaffold cultures. TD198946 and BMP-2 combination cultures showed higher chondrogenic differentiation than TD198946 or BMP-2 alone. The engineered cartilage maintained its extracellular matrices for four weeks post implantation. In contrast, engineered cartilage treated with either TD198946 or BMP-2 alone was mostly absorbed. CONCLUSIONS: Our results indicate that TD198946 could improve quality of engineered cartilage by redifferentiation of dedifferentiated chondrocytes pre-implantation and promoting collagen and glycosaminoglycan synthesis.